2015
DOI: 10.22495/cocv13i1c10p9
|View full text |Cite
|
Sign up to set email alerts
|

Ownership concentration and investment sensitivity to market valuation

Abstract: During the past decade, Jordan has undertaken substantial reforms aiming at restructuring its stock market in order to strengthen its role in promoting investment and allocating capital efficiently. This paper empirically investigates the impact of stock market development on capital investment at the firm level by assessing the investment-q sensitivity. In addition, this paper examines the impact of concentrated ownership, a salient institutional feature of listed Jordanian companies, on the investment-q sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Given our data on the shareholders of mines, we compute the Herfindahl–Hirschman index (HHI) of OC to capture the degree to which a mine has concentrated or diluted ownership (we call this variable ownership concentration ). As discussed above, previous research (e.g., Filatotchev et al, 2001; Tayem, 2015) has shown that there is a relationship between OC and investment behavior. To determine a measure between 0 and 1, we scale this variable by dividing it by 10,000 before running our regression models.…”
Section: Datamentioning
confidence: 78%
See 1 more Smart Citation
“…Given our data on the shareholders of mines, we compute the Herfindahl–Hirschman index (HHI) of OC to capture the degree to which a mine has concentrated or diluted ownership (we call this variable ownership concentration ). As discussed above, previous research (e.g., Filatotchev et al, 2001; Tayem, 2015) has shown that there is a relationship between OC and investment behavior. To determine a measure between 0 and 1, we scale this variable by dividing it by 10,000 before running our regression models.…”
Section: Datamentioning
confidence: 78%
“…The link between firm ownership and investments is an important research question. Ownership structure has been shown to be relevant for the responsiveness of investments to demand shocks (Maksimovic et al, 2017; Tayem, 2015). For instance, by mitigating or exacerbating agency problems (e.g., Bebchuk et al, 2015; Shleifer & Vishny, 1994), OC may impact investment–cash flow sensitivities.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Jordanian firms listed on Amman Stock Exchange (ASE) are mostly characterized by highly concentrated ownership structures and dominance of duality (Tayem, 2015). In addition, large owners assume managerial, which means that the largest shareholder usually performs the duties of the Chairman and/or the CEO.…”
Section: Institutional Environment and Corporate Ownership In Jordanmentioning
confidence: 99%
“…In addition, large owners assume managerial, which means that the largest shareholder usually performs the duties of the Chairman and/or the CEO. Therefore, in the case of Jordan, the largest shareholders become insiders rather than monitors (Tayem, 2015). Controlling owners have stronger incentives and greater power to extract private benefits for themselves in the form of higher compensations (Cheung et al, 2005).…”
Section: Institutional Environment and Corporate Ownership In Jordanmentioning
confidence: 99%
“…There is a priori cause to doubt a regular manipulation of earnings in Jordan, due to the nature of ownership structure of firms listed on Amman Stock Exchange (ASE). Jordanian listed firms are mostly characterized by highly concentrated ownership structures, which allows shareholders with large ownership stake to exercise control over the firm (Tayem, 2015). Therefore, managers of such firms have stronger incentives and greater power to act opportunistically for personal gain, and tend to get involved in unprofitable projects, over investments and misuse the funds (Jensen, 1986).…”
Section: Institutional Environment and Corporate Ownership In Jordanmentioning
confidence: 99%